Holography with higher-order Stokes correlations - Singh R.K. (My University, 2025)
Digital holography (DH) plays a significant role in non-destructive testing, and quantitative phase imaging [1]. Various geometries of the DH have been proposed and some of these are in-line, off-axis, and phase-shifting [1, 2]. The DH with correlations of the stochastic light fields has steered new trends and interests in the optical imaging [3-6]. This paper discusses role of coherence optics and two points complex correlations in the design and development of new holographic methods. © 2023 SPIE.